Simultaneous quantitative determination of celecoxib and its two metabolites using liquid chromatography-tandem mass spectrometry in alternating polarity switching mode - Oh, Hyun-A; Kim, Donghak; Lee, Soo Hyun; Jung, Byung Hwa (ELSEVIER SCIENCE BV, 2015)
A simple and rapid quantitative analytical method for the simultaneous detection of celecoxib and its two main metabolites, hydroxycelecoxib (celecoxib-OH) and celecoxib carboxylic acid (celecoxib-COOH), in rat plasma using liquid chromatography-tandem mass spectrometry (LC-MS/MS) was developed. The plasma sample was prepared through simple protein precipitation, and the reconstitution solution (0.1% formic acid in 50% methanol) was optimized to achieve the best peak shape and recovery. The analytes were separated using an Atlantis T3 column (2.1 mm x 100 mm, 3 mu m), and the mobile phase was composed of 10 mM ammonium formate in either 5% acetonitrile or 95% acetonitrile. The detection of the analytes was performed in alternating polarity switching mode using electrospray ionization. As celecoxib-OH and celecoxib-COOH were slightly unstable following freeze-thaw cycles and long-term storage at -80 degrees C in stability tests, every analysis was carefully conducted with one-freeze thaw cycle and a short storage duration (<1 week). Acceptable accuracy (<15%) and precision (<15%) were obtained in intra- and inter-day validations. The method was successfully applied to the pharmacokinetic study of celecoxib, celecoxib-OH and celecoxib-COOH following the oral administration of celecoxib in rats at a dose of 10 mg/kg. Comparing the related pharmacokinetic parameters of celecoxib and its metabolites, celecoxib was quickly metabolized into celecoxib-OH and subsequently converted to celecoxib-COOH in short intervals. The AUCs for the two metabolites were less than 10% of that for celecoxib, indicating that the rate of celecoxib metabolism was low. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: HUMAN PLASMA; CLINICAL PHARMACOKINETICS; COLORECTAL ADENOMA; COX-2 INHIBITORS; PREVENTION; EXCRETION; DISEASE; TISSUE; MS/MS